Cartilage Degradation in Psoriatic Arthritis Is Associated With Increased Synovial Perfusion as Detected by Magnetic Resonance Imaging - Abrar, Daniel B.; Schleich, Christoph; Müller-Lutz, Anja; Frenken, Miriam; Radke, K. Ludger; Vordenbäumen, Stefan; Schneider, Matthias; Ostendorf, Benedikt; Sewerin, Philipp (Frontiers in Medicine, 2020)
Objective: Even though cartilage loss is a known feature of psoriatic arthritis (PsA), research is sparse on its role in the pathogenesis of PsA and its potential use for disease detection and monitoring. Using delayed gadolinium-enhanced magnetic resonance imaging of cartilage (dGEMRIC) and dynamic contrast-enhanced MRI (DCE MRI), research has shown that early cartilage loss is strongly associated with synovial inflammation in rheumatoid arthritis (RA). The aim of this study was to determine if acute inflammation is associated with early cartilage loss in small finger joints of patients with PsA. Methods: Metacarpophalangeal (MCP), proximal interphalangeal (PIP), and distal interphalangeal (DIP) joints of 17 patients with active PsA were evaluated by high-resolution 3 Tesla dGEMRIC and DCE MRI using a dedicated 16-channel hand coil. Semi-quantitative and quantitative perfusion parameters were calculated. Images were analyzed by two independent raters for dGEMRIC indices, PsA MRI scores (PsAMRIS), total cartilage thickness (TCT), and joint space width (JSW). Results: We found significant negative correlations between perfusion parameters (except Kep) and dGEMRIC indices, with the highest value at the MCP joints (KTrans: τ = −0.54, p = 0.01; Kep: τ = −0.02, p = 0.90; IAUC: τ = −0.51, p = 0.015; Initial Slope: τ = −0.54, p = 0.01; Peak: τ = −0.67, p = 0.002). Heterogeneous correlations were detected between perfusion parameters and both, total PsAMRIS and PsAMRIS synovitis sub-scores. No significant correlation was seen between any perfusion parameter and JSW and/or TCT. Conclusion: As examined by DCE MRI and dGEMRIC, there is a potential association between early cartilage loss and acute synovial inflammation in small finger joints of PsA patients.